Pengaruh Tata Kelola Dana Desa Terhadap Kepuasan Masyarakat : Kampung Nawa Mulya - Wadjo, Dian Nurjannah; Syauta, Jack H.; Kambuaya, Quincy F. (Magister Manajemen Universitas Cenderawasih, 2025)
At the level of village government, the Village (Kampung) is a legal community unit that has the authority to regulate and manage the interests of the local community based on the origin and local customs recognized in the National Government system and located in the Regency area. The purpose of this study is to determine the influence of village fund governance (transparency, participation, and accountability) on the satisfaction of the people of Nawa Mulya Village, Yapsi District, Jayapura Regency. This research method uses quantitative research on descriptive design with T and F tests. Results There is an effect of village fund governance (transparency) (X1) on Community Satisfaction in NawaMulya Village, Yapsi District, Jayapura Regency. The higher the level of transparency, the higher the public satisfaction. There was an effect of village fund governance (participation) (X2) on Community Satisfaction in NawaMulya Village, Yapsi District, Jayapura Regency. The higher the level of transparency, the higher the public satisfaction. There was an effect of village fund governance (participation) (X2) on Community Satisfaction in NawaMulya Village, Yapsi District, Jayapura Regency. The higher the level of community participation, the higher the community satisfaction. There is an effect of village fund governance (accountability) (X3) on Community Satisfaction in NawaMulya Village, Yapsi District, Jayapura Regency. The higher the level of accountability, the higher the satisfaction of the community. Conclusion There is a significant influence between the variables of transparency, participation and accountability of fund management on community satisfaction in Nawa Mulya Village, Yapsi District, Jayapura Regency.